Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1038/sj.bjc.6601368
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of various cytological examinations by bronchoscopy in the diagnosis of peripheral lung cancer

Abstract: To improve the efficacy of fibreoptic bronchoscopy in the diagnosis of peripheral lung cancer, we evaluated the effectiveness of various techniques for obtaining samples for cytological examination. Between January 1984 and December 2000, flexible fibreoptic bronchoscopy under fluoroscopic guidance was performed in 1372 patients with lung cancer having no visible endoscopic findings. Histological examination of specimens obtained by forceps biopsy and cytological examinations on imprints of biopsy specimens, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
41
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 9 publications
(8 reference statements)
4
41
1
1
Order By: Relevance
“…Lung cancer was more frequently found in male subjects (77.2%), which is consistent with earlier findings [9][10][11]. Our results showed that there was a 3.39 times higher possibility of lung cancer in male subjects than in female subjects when they had WLB examination (Table1).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Lung cancer was more frequently found in male subjects (77.2%), which is consistent with earlier findings [9][10][11]. Our results showed that there was a 3.39 times higher possibility of lung cancer in male subjects than in female subjects when they had WLB examination (Table1).…”
Section: Discussionsupporting
confidence: 82%
“…Moreover, the incidence of squamous cell carcinoma was 54.5% in male and 15.6% in females. One possible explanation to this tendency is that men have much higher prevalence of smoking than women in China [10][11][12][13][14][15][16][17] . Chinese National Tobacco Prevalence Survey in 2002 reported current smoking prevalence of 57.4% for men and 2.6% for women [14].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately only a small part of the lungs can be inspected by FOB, and the diagnostic yield of bronchoscopy for peripheral lung tumours ranges between 36 and 52 per cent. Recent data from bronchoscopic examination for peripheral lesions under simultaneous fluoroscopic guidance for cytological or histological sampling, revealed an overall diagnostic yield of 93.4% [11]. Most of the lung tumours referred for surgical resection or other therapy have bronchoscopic evidence of malignancy, and so this procedure is believed to be the most successful method in the diagnosis of lung cancer [9,10].…”
mentioning
confidence: 99%
“…Bronchoscopy has a diagnosti c yield of more than 90% when combined with bronchial cytology and biopsy. 6,8 In this study, the most common tumor was squamous cell carcinoma 64.2%, followed by adenocarcinoma 18.8%, small cell carcinoma 13.2%, large cell carcinoma 1.9% carcinoid tumor 1.9% In 46 cases, brushing cytology were well correlated with biopsy which was taken as a gold standard. There were no cytologically false positi ve cases.…”
Section: Discussionmentioning
confidence: 88%